PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM QUIZ DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PADA MATA PELAJARAN FIQH PESERTA DIDIK KELAS V SDIT AL MAWADDAH WARRAHMAH KOLAKA - Susi Apryana; Muhammad Akbar; Hartono (Jurnal Teknologi Pendidikan Madrasah, 2024)
This research is motivated by student learning outcomes where in the learning process students are less active and pay less attention to explanations from their teachers, and there are some students who don't like the subject, and there are some participants who are lazy about doing assignments. So this can affect learning outcomes. This research uses the Team Quiz type cooperative learning model.The formulation of the problem in this research is (1) How is the Team Quiz type cooperative learning model implemented in the Fiqh subject for class V students at SDIT Al Mawaddah Warrahmah Kolaka? (2) What are the learning outcomes of students in the Fiqh subject by implementing the Team Quiz type cooperative learning model for class V SDIT Al Mawaddah Warrahmah Kolaka?, The research method used includes the type of classroom action research (PTK) with a quantitative approach. The research subjects are class V students at SDIT Al Mawaddah Warrahmah Kolaka. The research procedures carried out included four stages, namely: Planning, Implementation, Observation and Reflection, with data collection techniques in the form of observation, interviews, documentation and tests. The research instruments used student and teacher observation sheets, interview sheets, test sheets and documentation sheets. The research results show that the application of the Team Quiz type cooperative learning model has an effect on improving student learning outcomes. The increase in student learning outcomes occurred due to the correct implementation of the Team Quiz type cooperative learning model. Where students learn in a small group consisting of three people and work together with each other. The application of the Team Quiz type cooperative learning model is able to foster enthusiasm for working together with group friends so that it can improve student learning outcomes. This is proven by the increase in student learning outcomes, where in the pre-cycle student achievement reached 33%, in cycle I the achievement of student learning outcomes was 56%, while in cycle II the achievement of student learning outcomes was 90%.